Development of Android-based Javanese language “Pawarta” learning media using Adobe Animate software - Yusnita, Windi; Dwijonagoro, Suwarna (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
Javanese language learning aims to preserve regional languages ​​and introduce local cultural values ​​to the younger generation, especially in the midst of globalization that is shifting the use of Javanese. Understanding the material and motivation are challenges for students in learning Javanese. This is due to the lack of learning media. Therefore, this study discusses the development of Android-based learning media